The challenge of constructing an international XAFS database. (30th May 2018) - Asakura, Kiyotaka; Abe, Hitoshi; Kimura, Masao
Abstract : The present situation of the XAFS database in Japan and a proposal for the construction of an international collaboration XAFS database are presented. Abstract : The present state of XAFS databases, particularly in Japan, and proposals for future directions are presented. International collaboration is important for enlarging the database for further development of XAFS spectroscopy.